Women in the silent cinema : histories of fame and fate (2017)
This book presents the careers and oeuvres of three women filmmakers from the silent era, and two of them for the first time comprehensively in English language scholarship. Adriënne Solser, a comic actress and a producer of mixed stage and film shows in The Netherlands, is virtually unheard of in international scholarship. Musidora derived her fame in international film history and feminist theory from her roles as the female criminal in French crime series, but the large body of comic films in which she acted or the three dramas and the mixed stage and film production which she directed in France deserve much more consideration than they have so far received. With Nell Shipman, a Canadian born actress and filmmaker who used to work in the United States, the reverse is the case: the films she produced and directed were indeed the subject of historical and feminist research, but her acting career on the American popular stage or in the cinema were not. In this book, I reconstruct the full range of each career, as actresses and filmmakers in the silent cinema and as actresses in early twentieth century stage entertain- ment. Each career, moreover, is situated in its historical and national con- text. The oeuvres discussed each include an array of stage performances, a set of leading roles in films directed and produced by others, and a number of feature films and shorts produced and (co-) directed by the woman filmmaker in question.